1991
DOI: 10.1083/jcb.115.3.829
|View full text |Cite
|
Sign up to set email alerts
|

Expression of beta 1, beta 3, beta 4, and beta 5 integrins by human epidermal keratinocytes and non-differentiating keratinocytes.

Abstract: Abstract. We have compared the adhesive properties and integrin expression profiles of cultured human epidermal keratinocytes and a strain of nondifferentiating keratinocytes (ndk). Both cell types adhered to fibronectin, laminin, and collagen types I and IV, but ndk adhered more rapidly and at lower coating concentrations of the proteins . Antibody blocking experiments showed that adhesion of both cell types to fibronectin was mediated by the a5ß, integrin and to laminin by a 3ß1 in synergy with a2ß1 . Kerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
99
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(103 citation statements)
references
References 66 publications
4
99
0
Order By: Relevance
“…Basal keratinocytes do not normally express α v β 3 and α v β 6 integrins (Breuss et al, 1995;Haapasalmi et al, 1995). α v β 5 has been detected from the same areas of normal buccal mucosa (Adams and Watt, 1991). On the other hand, it has been also reported to be absent from normal gingival epithelium (Larjava et al, 1993).…”
mentioning
confidence: 87%
“…Basal keratinocytes do not normally express α v β 3 and α v β 6 integrins (Breuss et al, 1995;Haapasalmi et al, 1995). α v β 5 has been detected from the same areas of normal buccal mucosa (Adams and Watt, 1991). On the other hand, it has been also reported to be absent from normal gingival epithelium (Larjava et al, 1993).…”
mentioning
confidence: 87%
“…Rat proliferative keratinocytes also expressed integrin β1 and the expression was down-regulated by exogenous Ca 2+ . In contrast to the induction of desmosomal proteins, human keratinocytes decrease expression of integrin β1 protein and mRNA during differentiation [1,17,33]. These results suggested that keratinocyte integrins not only mediate adhesion to extracellular matrix but also regulate the initiation of the terminal differentiation.…”
Section: Discussionmentioning
confidence: 74%
“…64(2): 123-127, 2002 The epidermis consists of multiple layers of keratinocytes. When keratinocytes of the basal layer withdraw from the cell cycle and become committed to the terminal differentiation, they detach from the basement membrane and migrate into the suprabasal layers [1,6,7,12]. During the differentiation, human keratinocytes express several proteins, transglutaminase and substrates of this enzyme such as involucrin and filaggrin, which form the cornified envelope in the keratinized layer of the epidermis.…”
mentioning
confidence: 99%
See 2 more Smart Citations